(untitled) (Revista NUPEART, 2026)
The article discusses the integration of art into Early Childhood Education through the Parangolé Workshop, inspired by the work of Hélio Oiticica. The proposal, grounded in the ideas of John Dewey and in the a/r/tographic approach of Dias and Irwin, employed non-conventional materials and bodily movement as legitimate forms of artistic expression. By valuing free aesthetic experimentation, the practice expanded children’s sensory and creative perceptions. The results highlight art as a transformative pedagogical tool that promotes meaningful and sensitive learning. The study further emphasizes the importance of contemporary art in the Early Childhood Education curriculum, as it fosters children’s holistic development and authentic expression.